Epithelial dysplasia in gastric endoscopic biopsies - Adem ARSLAN; Mehmet MÜDERRİSZADE and Hüseyin BÜYÜKBAYRAM and A. Kemal UZUNLAR and Fahri YILMAZ and A. Rahman IŞIKAKDOĞAN and İbrahim SARI and Ö. Mehmet ÖZAYDIN (Turkish Journal of Gastroenterology, 2019)
-